Corruption and the business environment in Viet Nam: An exploratory survey - Daisuke Maruichi; Masato Abe (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2018)
This paper examines the effect of corruption on the business environment in Viet Nam. Our survey of firms operating in Viet Nam suggests that corruption is perceived as the most severe business constraint for their operation. Also, corruption has a significant negative association with the overall satisfaction of the business environment in Viet Nam. Such results support the hypothesis that corruption has a "sand the wheel" effect on firms' business activities. While this paper sheds light on the importance of corruption, it would be useful to conduct follow-up studies to examine corruption and its impact in more detail. Such studies could be conducted in those segments that most severely suffer from corruption according to our survey, i.e., medium-sized enterprises, hotel/restaurant and construction sectors, Hanoi based, and Vietnamese owned firms.
Keywords: H11; L20; 330; business environment; business constraint; corruption; Viet Nam